(untitled) (Research, Society and Development, 2022)
Introduction: Although there have been changes in the composition of composite resins aimed at reducing failures in restorations, there is currently a lack of consensus in the literature about its longevity and long-term survival of this material in anterior teeth. Objective: to investigate the clinical longevity of anterior composite resin restorations. Methodology: Following the PRISMA Statement Guidelines, an integrative peer review of the literature was carried out. The articles were indexed in the Pubmed database, based on the search with the descriptors “resin” and “clinical performance”. Results: 17 original articles were included in the study, predominantly in English. The most prevalent study design in the analyzed articles was the prospective one, totaling 80,470 restorations in this study. Conclusion: Direct composite resin restorations have a good longevity of up to 11 years, however, the technique is not immune to local fractures, therefore requiring care such as the use of protective plates and cementation of fiberglass posts.